A door-to-door health education focusing on stunting in Petung Village, Pakis, Magelang District - Sumarno Adi Subrata; Fida Aufa Ammaralia; Nabilla Agesta La'ali; Melinda Nuria Iffana; Sella Indah Nugraeni; Nuri Apitriyana (Universitas Muhammadiyah Magelang, 2022)
Education is a pillar in handling health problems, including stunting. This problem is being complained by residents in Petung Village, Pakis, Magelang Regency. Some data show that 41 children suffer from stunting. However, now there are 13 children. Although the number has decreased, some residents are still worried that the number of cases will continue to increase. Based on these data, the Integrated Community Service Program (PPMT) was implemented to address the stunting phenomenon and its prevention. This program is carried out door-to-door in order to reduce the risk of exposure to Covid-19 virus infection. The community is very responsive when the discussion takes place and asks a lot of questions. This activity is expected to be a support for the government's program to eradicate stunting in Petung Village.